Evaluation of drug use in rheumatoid arthritis patients at the outpatient installation of Dr. H. Abdul Moeloek Bandar Lampung Regional Hospital - Dewi Suci S. Riadi; Nurul Irna Windari; Gayatri Simanullang (Sasambo Journal of Pharmacy, 2026)
Rheumatoid Arthritis (RA) is an autoimmune disease characterized by the main symptoms of pain, swelling, stiffness in the joints and joint inflammation. Joint pain in RA can reduce quality of life and can interfere with work and social activities. This study aims to determine the characteristics of rheumatoid arthritis patients and analyze the evaluation of drug use in rheumatoid arthritis patients in the outpatient installation of RSUD Dr. H. Abdul Moeloek Bandar Lampung. This research is non-experimental in nature using data collection techniques in the form of purpose sampling. The patient population studied was aged ≥ 18 years with a minimum sample size of 65 patients. The results of research regarding the characteristics of rheumatoid arthritis patients in the outpatient installation of RSUD Dr. H. Abdul Moeloek Bandar Lampung showed that RA patients were dominated by age 40-50 years as much as 35% with female gender as much as 86.15%, and consuming methotrexate as much as 78% with the most symptoms being pain as much as 97% and accompanied by hypertension as comorbidities were 12.3%. Evaluation of drug use in rheumatoid arthritis patients in the outpatient installation of Dr. H. Abdul Moeloek Bandar Lampung Hospital obtained rationality results of 9.2% irrational and 90.8% rational with categories of appropriate indications of 100%, appropriate drugs of 100%, appropriate dosage of 90.7%, and appropriate patients of 100%.